Transition towards a tourist innovation model: The smart tourism destination:reality or territorial marketing? - Enrique Sigalat-Signes; Ricard Calvo-Palomares; Bernat Roig-Merino; Iván García-Adán (Journal of Innovation & Knowledge (JIK), 2020)
Implantation of the smart city model in intermediate tourist towns on their transition to becoming smart destinations involves an inescapable commitment to their habitat and improving the quality of civic life and the economy of cities through more sustainable and technologically advanced elements. Based on this work, the aim is to achieve an overview of the current smart cities paradigm from the standpoint of territorial interest groups, by analysing a tourist town on the Mediterranean coast (Gandia, Valencia) to diagnose its current status. The ultimate aim is to answer the question of whether these intermediate tourist cities are in a position to align themselves with the necessary requirements of the smart model, in their transition to becoming smart tourism destinations.
Keywords: 650; Smart city; Intermediate cities; Gandia; Smart tourist destination; Innovation; Stakeholders